2006
DOI: 10.1002/jnr.21114
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic regulation of neuronal nitric oxide synthase expression in the rat amygdala: Functional role for nitric oxide in adaptive responses?

Abstract: Water-deprivation-induced osmotic stress leads to activation of a number of adaptive responses. Nitric oxide (NO) has been implicated in the modulation of these responses, as the amygdala has been implicated in ingestive behavior and modulation of autonomic homeostatic functions. Here we investigated the effects of water deprivation on neuronal nitric oxide synthase (nNOS) expression within the rat amygdala; a brain area involved in modulating ingestive behavior and autonomic function. Water deprivation result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…At the end of the plus maze test, animals were allowed to drink water freely, and the respective intakes at 30 and 120 minutes (Figures 7A, B and Supplementary Table 6) were recorded. As expected, water-deprived rats drank more water than the control animals at 30 and at 120 minutes [F (1,33) =504.8; p<0.0001 and F (1,33) =521.4; p<0.0001; respectively]. However, the oxytocin receptor antagonist had no effect on the water drank by the rats (Figures 7A, B).…”
Section: Effect Of Oxtr Antagonist Microinjection In Ceasupporting
confidence: 67%
“…At the end of the plus maze test, animals were allowed to drink water freely, and the respective intakes at 30 and 120 minutes (Figures 7A, B and Supplementary Table 6) were recorded. As expected, water-deprived rats drank more water than the control animals at 30 and at 120 minutes [F (1,33) =504.8; p<0.0001 and F (1,33) =521.4; p<0.0001; respectively]. However, the oxytocin receptor antagonist had no effect on the water drank by the rats (Figures 7A, B).…”
Section: Effect Of Oxtr Antagonist Microinjection In Ceasupporting
confidence: 67%
“…The reasons for this difference are presently unknown. Water deprivation represents a globally stressful experience for individuals, and BLA is an important region for stress responses [57][58][59]. Therefore, it is tempting to speculate that the cortical control of BLA activity might mitigate the stress component induced by water deprivation.…”
Section: Acc Neurons Projecting To Bla: a Novel Locus For Control Of ...mentioning
confidence: 99%
“…In the amygdala, NO is additionally linked with modulation of anxiety levels and other emotional processes (Shindou et al, 1993, Yao et al, 2007). It should be noted that the largest neurons in the primate IM were NOS+, and a recent study showed that large IM neurons — which are distinct from small spiny IM neurons — relay noxious sensory information, and can innervate other inhibitory neurons in basal and lateral amygdalar nuclei (Bienvenu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%